The explicit formula for a sequence isan= −2 + 3/2 (n − 1)

What is the 21st term of the sequence?

Answers

Answer 1
Answer:

Answer:

28

Step-by-step explanation:

Let n = 21, and evaluate the expression.

a_n = -2 + (3)/(2)(n - 1)

a_(21) = -2 + (3)/(2)(21 - 1)

a_(21) = -2 + (3)/(2)(20)

a_(21) = -2 + (3)/(1)(10)

a_(21) = -2 + 30

a_(21) = 28


Related Questions

Leah ran 6 block north then back 4 block south
Two problems here- 1) Find the total cost to the nearest cent, $100 dinner; 20% gratuity 2) Find the total cost to the nearest cent, 12300 car; 5% sales tax
[(25-11)+(15-9)] divided by 5
Factorizar 2x^2-3xy-4x+6y
Rhonda earned 324.65 delivering newspapers. She promised her sister 0.2 of her earnings for helping her. How much does Rhonda owe her sister?

What is the least amount of acute angles a triangle can have?

Answers


A triangle can have one, or two, or three acute angles.
It must have at least one of them.
That's the least.

-3y4-5y3+17y2+9y+1/0.5y2

Answers

Answer:

If you are combining like terms your answer will be -3y^4-5y^3+19y^2+9y

Step-by-step explanation:

Whats 600*50000+60 to this math problem

Answers


Let's see -

Wow! You'll be surprised to see how big your answer will be!

600 × 50,000 = 30,000,000

30,000,000 + 60 = 30,000,060

Final answer -

30,000,060

WOW! Big, right? :)

↑   ↑   ↑  Hope this helps! :D

find three consecutive integers such that the sum of the first and twice the second is equal to the third plus four​

Answers

Answer:

The three consecutive integers are 2,3,4

Step-by-step explanation:

Let the three consecutive integers be represented as x,x+1,x+2

As per the given condition, the sum of the first and twice the second integer is equal to the third integer plus 4.

Representing it in the form of an equation:

x + 2*(x+1) = (x+2) + 4

=> x + 2x + 2 = x+6

=> 3x + 2 = x + 6

=> (3x -x) = 6 - 2

=> 2x = 4

=> x = 4/2 = 2

So the three integers are 2,3,4

Verification: 2 + 2*3 = 8

                    4 + 4 = 8

So the requirement is satisfied by these integers.

Ax+By=C form help...

Answers

Answer:

4x-y= -18

Step-by-step explanation:

y-1=4(x+4)

y-1=4x+16

4x-y=-1-17

4x-y=-18

where A=4 B=-1 and C=-18

Answer:

4x + y = -15

Step-by-step explanation:

y - 1 = -4(x+4)

y - 1 = -4x - 16

y = -4x - 16 + 1

y = -4x - 15

4x + y = -15

Please help! Would you describe the associations in this table as… (pick two)Linear? Negative? Nonlinear? Positive?



I know it would be nonlinear because neither Variable X OR Y have a constant rate of change.
Unfortunately, I don't know whether it is positive or negative.

Answers

i would say negative